Pengaruh Kompetensi dan Integritas Auditor terhadap pendeteksian Fraud Financial Statements - Siti Nafilah Rahmat; Pupung Purnamasari; Nopi Hernawati (UNISBA Press, 2022)
Abstract This study aims to determine the effect of competence and integrity of auditors on the detection of fraudulent financial statements. This research was conducted at the Public Accounting Firm in Bandung with a sample of 32 respondents. The method used in this study is a descriptive method with a quantitative approach. The data source used is the primary data source with the data collection technique used is a questionnaire. The sample in this study used a non-probability sampling method with purposive sampling technique. The hypothesis testing used is multiple linear regression analysis with SPSS version 23 statistical tool. From the results of the tests carried out, the results of the study indicate that (1) Auditor Competence has a significant effect on detecting fraud in financial statements, (2) Auditor Integrity has a significant positive effect on fraud financial statements. Suggestions for further researchers can add respondents from other big cities, in order to find out and prove how much competence and integrity of auditors affect the detection of financial statement fraud in other big cities. So it is advisable to add other variables or other factors to detect fraudulent financial statements. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi dan integritas auditor terhadap pendeteksian fraud financial statements. Penelitian ini dilakukan pada Kantor Akuntan Publik di Kota Bandung dengan sampel yang diperoleh 32 responden. Sumber data yang digunakan adalah sumber data primer dengan teknik pengumpulan data yang digunakan adalah kuesioner. Sampel yang digunakan adalah metode non-probability sampling. Dari hasil pengujian yang dilakukan, hasil penelitian menunjukkan bahwa (1) Kompetensi Auditor berpengaruh signifikan terhadap Pendeteksian fraud financial statements, (2) Integritas Auditor berpengaruh positif signifikan terhadap Pendeteksian fraud financial statements. Saran bagi peneliti selanjutnya dapat menambah responden dari kota-kota besar lainnya, agar dapat mengetahui dan membuktikan seberapa besar kompetensi dan integritas auditor yang berpengaruh terhadap pendeteksian fraud financial statements di kota-kota besar lainnya. Kemudian disarankan untuk menambah variabel lain atau faktor-faktor lain terhadap Pendeteksian fraud financial statements.